Factors associated with adverse pregnancy outcomes in women with systematic lupus erythematosus. (February 2018) - Deguchi, Masashi; Maesawa, Yoko; Kubota, Shino; Morizane, Mayumi; Tanimura, Kenji; Ebina, Yasuhiko; Yamada, Hideto
Highlights: A history of recurrent pregnancy losses increased risks of pregnancy loss in SLE women. Low complements and antiphospholipid syndrome increased risks of premature delivery. Two or more positive antiphospholipid antibodies increased risks of premature delivery. Prednisolone therapy >14 mg/day increased risks of HDP. Low dose aspirin therapy decreased risks of LFD neonate. Abstract: The aim of this prospective study was to determine clinical factors associated with adverse pregnancy outcomes in women with systematic lupus erythematosus (SLE). Fifty-six pregnancies from 46 women with SLE were enrolled. Risk factors for pregnancy loss, premature delivery, hypertensive disorders of pregnancy (HDP), and light-for-date neonate (LFD), were evaluated. Univariate and multivariate logistic regression analyses revealed a history of two or more pregnancy losses before 10 gestational weeks (GW) (OR 11.5, 95%CI 1.72–76.8) as a risk factor for pregnancy loss; low levels of blood complements (OR 7.55, 95%CI 1.10–51.9) and antiphospholipid syndrome (OR 26.5, 95%CI 3.17–219) as risk factors for premature delivery before 37 GW; SLEDAI score at conception (OR 1.68, 95%CI 1.05–2.68) and positive tests for two or more antiphospholipid antibodies (OR 6.89, 95%CI 1.13–41.9) as risk factors for premature delivery before 34 GW; prednisolone therapy >14 mg/day (OR 7.55, 95%CI 1.10–51.9) as a risk factor for HDP; and low dose aspirin therapy (OR 0.21, 95%CI 0.05–0.97) decreased the risk for LFD neonate. These results have important implications for clinicians managing SLE complicated pregnancy.